Anthrone-spirolactam and quinoline hybrid based sensor for selective fluorescent detection of Fe(3+)ions - Darole, Ratanamala S.; Christopher Leslee, Denzil Britto; Mukherjee, Anagh; Gonnade, Rajesh G.; Karuppannan, Sekar; Senthilkumar, Beeran (2020)
The synthesis of a novel, and highly selective Fe(3+)ion sensor based on anthrone-spirolactam and its quinoline hybrid ligand is reported. The designed ligand displayed selective detection of Fe(3+)ions with enhanced fluorescence emission. The complexation of Fe(3+)ion led to a red shift of 32 nm from 420 nm to 452 nm, and a several fold increase in intensity with fluorescent green emission. The complexation (detection) of Fe(3+)ions with ligand resulted in chelation enhanced fluorescence and intramolecular charge transfer through the inhibition of C=N isomerization. This hybrid sensor shows high sensitivity and selectivity, spontaneous response, and works on a wide pH range a minimum detection limit of 6.83 x 10(-8)M. Importantly, the sensor works through the fluorescence turn-on mechanism that overcomes the paramagnetic effect of Fe(3+)ions. The binding mechanism between the ligand and the Fe(3+)ions was established from the Job's plot method, optical studies, Fourier transfor infrared spectroscopy, NMR titration, fluorescence life-time studies, and density functional theory optimization. The sensor displayed excellent results in the quantification of Fe(3+)ions from real water samples. Furthermore, due to its biocompatibility nature, fluorescent spotting of Fe(3+)ions in live cells revealed its bioimaging applications.
Keywords: anthrone-spirolactam-quinoline; Cell imaging; fluorescence; intramolecular charge transfer; iron

Synthesis of novel rhodamine type anthrone Spiro-lactam (ASL) analogues and evaluation of antiviral activity against dengue and chikungunya viruses - Darole, Ratanamala S.; Bagad, Pooja K.; Gonnade, Rajesh G.; Alagarasu, Kalichamy; Punekar, Madhura; Shukla, Shridhar; Parashar, Deepti; Senthilkumar, Beeran (European Journal of Medicinal Chemistry, 2023)
A series of Rhodamine type Anthrone-Spirolactam (ASL) derivatives Benzylimin-Anthrone-Spirolactam (ASL-1 to ASL-10) and Benzamide-Anthrone-Spirolactam (ASL-11 and ASL-12) were synthesized via a simple condensation reaction between Anthrone Spiro-lactamine (2) and various aromatic aldehyde and acyl chlorides respectively. Since rhodamine-based compounds were reported to have antiviral activity, the ASL derivatives were examined for in vitro antiviral activity against dengue and chikungunya viruses. Among all the analogues, ASL-3, ASL-6, ASL-7, ASL-8, ASL-9 and ASL-10 were the most potent against dengue virus (DENV) and exerted around one log reduction in virus titre under post -treatment conditions. At the same time ASL-3 was effective under cotreatment conditions. Two analogues ASL-6 and ASL-12 exerted anti-chikungunya virus (CHIKV) activity under post -treatment conditions. In silico docking studies revealed that the ASL derivatives interacted with the proteins of DENV and CHIKV. Together, the results suggest the anti-DENV and CHIKV activity of ASL derivatives which may be exploited further for therapeutic purposes.
Keywords: Anthrone Spiro-lactam; Chikungunya virus; dengue virus; Rhodamine

Brønsted acid- and Ni(ii)-catalyzed C-H oxidation/rearrangement of cyclotriveratrylenes (CTVs) to cyclic and acyclic quinones as potential anti-cancer agents - Darole, Ratanamala S.; Choudhary, Shailendra Singh; Sharma, Himanshu; Mali, Bhupendra P.; Gopu, Booblan; Vanka, Kumar; Senthilkumar, Beeran (Organic and biomolecular chemistry, 2024)
This paper describes a simple and practical protocol for the direct synthesis of acyclic and cyclic quinone derivatives via an acid-promoted nickel(ii)-catalyzed inner rim C-H oxidation of cyclotriveratrylene (CTV) and its analogues. The cyclic quinone derivatives resulted from trimethoxy-cyclotriveratrylene (TCTV) through C-C bond formation via intramolecular ipso substitution followed by subsequent anionic rearrangement containing stereo-vicinal quaternary centers. The DFT calculations strongly support the experimental findings and reveal the role of Bronsted acids in the C-H bond activation of CTV. All the newly synthesized compounds were screened for their in vitro anti-cancer activity using colorimetric SRB assay analysis. Among them, compounds 3a, 3d, 3h, 4a, 4b, 4c and 4e exhibited moderate anticancer activity against A549, HCT-116, PC-3, MDA-MB-231, HEK-293 and SW620 human cancer cell lines.

Highly selective C-N and C-S dual functionalization of 1,3-dicarbonyl derivatives using TBHP as an oxidant - Bagad, Pooja K.; Darole, Ratanamala S.; Krishna, G. Rama; Senthilkumar, Beeran (Journal of Organic Chemistry, 2024)
A direct electrosynthesis/photocatalyst-free, atom-economical, and efficient method for the selective synthesis of (E)-3-amino-2-thiocyanato-alpha,beta-unsaturated carbonyl compounds is described through a given protocol. The present approach features the use of inexpensive ammonium thiocyanate to achieve dual functionalization of 1,3-dicarbonyl compounds using TBHP as an oxidant, providing a rapid and practical route to the selective formation of both C-N and C-S bonds via a radical process. This method offers a broad substrate scope with excellent yield and allows for further exploration of the products to construct heterocyclic compounds and other functionalities.

Base mediated approach for the synthesis of deoxybenzoins using γ-aryl-β-ketoesters and benzoyl chlorides - Choudhary, Shailendra Singh; Darole, Ratanamala S.; Krishna, Gamidi Rama; Senthilkumar, Beeran (RSC Advances, 2025)
This study introduces a one-pot, transition metal-free strategy for synthesizing deoxybenzoins, overcoming the challenges of conventional methods. The reaction involves dual acylation of gamma-aryl beta-keto esters using K2CO3 in dioxane at 90 degrees C, followed by a concerted transformation to form deoxybenzoin. The protocol operates under mild conditions, tolerates a broad range of substrates, and produces minimal by-products, making it a practical, scalable alternative for accessing pharmaceutically relevant deoxybenzoins.